Analisis Hubungan Belanja Modal dan Belanja Pemeliharaan pada Anggaran Pemerintah Kabupaten Malang - Setiyawan, Erik; Junaidi, Junaidi; Sari, Arista Fauzi Kartika (Universitas Islam Malang, 2023)
Indonesia entered the era of regional autonomy with the implementation of Law Number 32 of 2004 concerning Regional Government which was later changed to Law Number 23 of 2014 and Law Number 25 of 1999 (later to become Law Number 33 of 2004) concerning Financial Balance between Central and Regional Governments. The application of financial balance between the central government and regional governments in Indonesia is reflected in the administration of government and public services which are based on the principles of de-centralization, de-concentration and co-administration. Capital expenditures are expenditures whose useful life exceeds one fiscal year and will add regional assets or wealth, as well as the consequences of increasing routine expenditures such as maintenance costs. Fixed assets obtained as a result of the realization of capital expenditures are used for the daily operational activities of a work unit, not for sale. The method used in this study is a qualitative method, namely by explaining the ways of collecting accurate and actual quantitative data. The samples used in this study were 18 selected districts in Malang Regency, both districts from 2019 to 2020. The analysis used was descriptive analysis and analysis of the Correlation Coefficient/Pearson Correlation. There is a strong and positive relationship between capital expenditure for the 2019 fiscal year and maintenance expenditure for the following fiscal year 2020. This means that the local government's decision to increase the amount of capital expenditure budget has been accompanied by an increase in the amount allocated for maintenance expenditure.Keywords: Capital expenditure, maintenance expenditure, positive relationship